2015
DOI: 10.4274/mirt.53215
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Helicobacter Pylori Infection in School and Pre-School Aged Children with C-14 Urea Breath Test and the Association with Familial and Environmental Factors

Abstract: Objective:To investigate the prevalence of Helicobacter pylori (Hp) infection in pre-school and school age children with C-14 urea breath test, and to explore its association with age and socioeconomic factors in Turkey.Methods:Hp infection status was determined by using Urea Breath Test (UBT). Patients who had previous gastric surgery, Hp eradication treatment or equivocal UBT results were excluded. A questionnaire was administered to elicit information on gender, age, ABO/Rh blood group type, presence of gas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
1
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 23 publications
0
5
1
1
Order By: Relevance
“…This value is similar to those reported in Iran (19.8%) [ 13 ], but higher than 15.1% reported in Taiwan [ 8 ]. However, our finding was lower than 27.4% reported in Saudi Arabia [ 14 ] and 49% in Turkey [ 15 ]. Reports presented in this study, together with reports of others, indicate that there is quite a variation in prevalence of H. pylori infections all around the world.…”
Section: Discussioncontrasting
confidence: 94%
See 1 more Smart Citation
“…This value is similar to those reported in Iran (19.8%) [ 13 ], but higher than 15.1% reported in Taiwan [ 8 ]. However, our finding was lower than 27.4% reported in Saudi Arabia [ 14 ] and 49% in Turkey [ 15 ]. Reports presented in this study, together with reports of others, indicate that there is quite a variation in prevalence of H. pylori infections all around the world.…”
Section: Discussioncontrasting
confidence: 94%
“…In contrary to these findings, a study carried out in Yemen found that girls were more affected than boys [ 21 ]. However, elsewhere studies showed no differences in the prevalence of infection between boys and girls [ 15 , 17 ].…”
Section: Discussionmentioning
confidence: 96%
“…In a large cohort of Brazilian children H. pylori was investigated by rapid urease test and postivity decreased from 60.4 to 30. 4 Some weak points of the study need to be addressed. Nearly half of the pathology reports of antral biopsies in group 1 could not be reached due to archiving problems but as the reports were lost randomly, we think it is still not a biased sample.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent nationwide epidemiological study in Turkey among adults, H. pylori prevalence was 82.5% 3 . Most recent H. pylori prevalence study involving Turkish children have reported a prevalence of 49% 4 .…”
mentioning
confidence: 99%
“…9 H. pylori gastritis has been determined in 6% of children with EE, a lower figure than in population-based H. pylori prevalence studies. 10 An inverse association has been reported between H. pylori infection and EE in previous pediatric studies. 11,12 H. pylori infection reduces the development of atopy by approximately 20%, which is protective against IgE mediated reactions.…”
Section: T H I S S T U D Y D E S C R I B E S ( I ) T H E C L I N I C mentioning
confidence: 85%